Linguistic nature of the terminological system of the beauty industry - Mambetova Manshuk, Akmaral Kurmanayeva,; Akilbayeva, Gulnar; Bayalieva, Gulmira; Abenova, Lazzat (Opción, 2019)
The paper focuses on various applications of the terms related to the Beauty industry in communication, as well as its regulation at the professional level, and deals with the linguistic nature of the terminological system of Beauty industry in the Kazakh Language via compilation, statistical, constructive, and analytical approaches. As a result of the analysis of the dominant terms in the terminological system of women’s cosmetics related to the Beauty industry in the Kazakh language were defined. In conclusion, the sub-groups within thematic groups are hierarchical micro-systems characterized by the terms that define the specific forms of cosmetic terminology.